Implementation of Physics Education Technology (Phet) Media on Student’s Science Concept Understanding: A Literature Review - Putri, Neli Suryani; Resti Yektyastuti; Yusuf Safari (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Physics Education Tehcnology (Phet) media has been widely utilized in science learning which helps students in understanding abstract concepts more easily. The purpose of this literature study is to ascertain whether Phet media can contribute to improving students' understanding of science concepts more significantly. This research uses a literature review methodology. The results of the review show that Phet media has significant potential to improve students' understanding of science concepts. Phet's interactive and visual simulations assist students in developing deeper and lasting understanding and encourage them to learn actively and independently. Overall, this literature study supports the use of Phet media in science learning to improve concept understanding and learning quality.